Patterns of Substance use and Its Predictors Among North-West University Students Mafikeng Campus - Osuafor, Godswill N.; Maputle, Sonto M.; Ayiga, Natal (African Journal of Drug and Alcohol Studies, 2016)
The aim of this study was to examine the pattern of substance use among university students in South Africa. A cross-sectional study of randomly selected 416 students was conducted. Data were analysed using descriptive statistics and binary logistic regression. The result of the study indicated that current alcohol use was reported by 67.5%, Cigarette, 21.4%, cannabis, 17.3% and glue 2.9%. Alcohol consumption was associated with sex, age, religious affiliation, home language, family influence, and substance experimentation. Sex and substance experimentation were predictors of cigarette smoking. Cannabis use was associated with respondent’s sociocultural group and family influence. There is need to strengthen the family structure of homes as present substance use is rooted in family influences. Educational programmes that emphasise the dangers of experimenting with substance to young people may have great potential in minimizing substance use.
Keywords: pattern; psychoactive; substance use; peer pressure